The Principal's Role in Improving the Quality of Islamic Religious Education in Junior High Schools/MTs - Indah Lestari; Ragil Arwani; Supriyatmoko Supriyatmoko (Al-Bustan: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the role of the school principal in efforts to improve the quality of Islamic religious education at SMP PGRI 2 Selagai Lingga. Using a qualitative approach with a case study method, data were collected through interviews, observations, and documentation. The findings reveal that the principal plays a significant role as an educator, supervisor, and manager through programs such as Quranic reading sessions, dhuha prayer, and religious sermons designed to improve student morality. Additionally, the principal involves the teaching council in supervision and skill enhancement, including the use of technology in learning. The implications of this study emphasize the importance of the principal's role in creating a conducive and integrated educational environment based on Islamic principles.